Activities of Antioxidant Enzymes in Six Rice (Oryza sativa L.) Varieties at Seedling Stage under Increasing Salinity Stress - D., Rajkumar; S, Gangadhar Rao; B., Tirupathi; H., Gonzalez Rodriguez (International Journal of Economic Plants, 2022)
Present study deals with the activities of antioxidant enzymes in six rice (Oryza sativa L.) varieties, namely Sadamota, Patnai, Dhoodeshwar, Ghewas, Gontrabidan-2 and Malabati, which were subjected to increasing salinity stress (0.05 M, 0.1 M and 0.15 M NaCl) from germination to seedling stage along with control under laboratory conditions. The main objective of this study was to find out variations in the activities of antioxidant enzymes which can differentiate tolerance to salinity. Increasing salinity stress induced gradual increase in the activity of Superoxide dismutase (SOD), Peroxidase, Catalse (CAT), Glutathione reductase (GR), and Ascorbate peroxidase (APX). High activities of SOD, CAT, GR and APX were observed in Doodeshwar and Malabti under salinity stress. High levels of antioxidant enzymes (SOD, CAT, APX and GR) under salinity stress will contribute to salinity tolerance in rice varieties Doodeshwar and Malabathi. Significant genotype×salt treatment interaction suggested the differential effect of stress on genotype for antioxidant enzymes. Catalse activity showed significant (p<.001) positive correlation with SOD (r=.818), GR (r=.624), and APX (r=.593). High levels of Lipid peroxidation was noticed in Ghewas, Gonrabidan-2 and Sadamota, indicating higher membrane damage when compare to Doodeshwar and Malabathi under salt stress. Doodeshwar and Malabathi can be recommended as salt tolerant varieties for advance evaluation at field level. Analysis of antioxidant enzymes from rice seedlings exposed to salinity stress will provide rapid screening method and time saving. Mass screening will be conducted for preliminary selections which can be used in field conditions.